2020
DOI: 10.1109/jphot.2020.2997935
|View full text |Cite
|
Sign up to set email alerts
|

2.5 kW Narrow Linewidth Linearly Polarized All-Fiber MOPA With Cascaded Phase-Modulation to Suppress SBS Induced Self-Pulsing

Abstract: As a major limitation for power scaling of high power narrow linewidth fiber master oscillator power amplifiers (MOPAs), Stimulated Brillouin Scattering (SBS) induced selfpulsing in polarization maintaining (PM) fiber amplifiers is well characterized and analyzed in this paper by comparing different white noise signal (WNS) phase-modulated modes in experiments. It is found that the self-pulsing effect is not observed in the PM-amplifier with single-frequency laser seed injection, and cascaded WNS modulation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The tailoring of laser line-shape with the proposed DMSN was initially investigated through simulations based on phase modulation. Transfer function of the phase modulator was used to incorporate the proposed modulation scheme and the spectra of filtered white noise was utilized to synthesize instances of noise voltage [29]. Sinusoid voltage is added to the noise to analyze the laser line-shape evolution for the proposed DMSN scheme with increasing sinusoidal power (1 GHz tone) as shown in Fig.…”
Section: Simulations and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The tailoring of laser line-shape with the proposed DMSN was initially investigated through simulations based on phase modulation. Transfer function of the phase modulator was used to incorporate the proposed modulation scheme and the spectra of filtered white noise was utilized to synthesize instances of noise voltage [29]. Sinusoid voltage is added to the noise to analyze the laser line-shape evolution for the proposed DMSN scheme with increasing sinusoidal power (1 GHz tone) as shown in Fig.…”
Section: Simulations and Experimental Setupmentioning
confidence: 99%
“…Improved power scaling using multiple modulation blocks in cascade has been demonstrated previously in [27] using nonpolarization maintaining (non-PM) architecture and in [28,29] with fully polarization maintaining (PM) architectures. In [28] the authors use cascaded sinusoidal modulation and demonstrate 3-dB spectral linewidth and output powers of 6 GHz and 477 W (single-stage), 18.5 GHz and 1040 W (twostage) and 45 GHz and 1890 W (three-stage modulation) respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous theoretical and experimental research on mitigating the SBS effect in fiber lasers and amplifiers has been conducted to prevent instability and physical damage to the laser system [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. As a case in point, in 2020, Wang et al demonstrated a 2.5 kW narrow linewidth linearly polarized MOPA by efficient suppressing of SBS-induced self-pulsing (SP) via implementing cascade phase modulation [54]. In the same year, they presented the first 3 kW all-fiber narrow linewidth linearly polarized MOPA via a bi-directional pumping scheme [55].…”
Section:  Stimulated Brillouin Scattering Effectmentioning
confidence: 99%
“…Numerous theoretical and experimental studies on mitigating the SBS effect in fiber lasers and amplifiers has been conducted to prevent instability and physical damage to the laser system [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. As a case in point, in 2020, Wang et al demonstrated a 2.5 kW narrow linewidth linearly polarized MOPA by efficient suppressing of SBS-induced self-pulsing (SP) via implementing cascade phase modulation [54]. In the same year, they presented the first 3 kW all-fiber narrow linewidth linearly polarized MOPA via a bi-directional pumping scheme [55].…”
mentioning
confidence: 99%